2009
DOI: 10.1002/jmv.21465
|View full text |Cite
|
Sign up to set email alerts
|

Mother to child transmission of HIV‐1 in a Thai population: Role of virus characteristics and maternal humoral immune response

Abstract: The objective of this study was to investigate factors influencing mother to child transmission of HIV-1 in Thailand, where HIV-1 CRF01_AE, the major subtype in Southeast Asia, predominates. Samples from 84 HIV-1 infected, anti-retroviral treatment-naïve, non-breast feeding mothers, 28 who transmitted HIV-1 to their babies (transmitters) and 56 who did not (non-transmitters), were studied for maternal humoral immune response and virus characteristics. Maternal humoral immune response was measured by lymphocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 67 publications
1
6
0
Order By: Relevance
“…In support of this hypothesis, previous studies reported that viruses transmitted during breastfeeding are usually resistant to maternal autologous neutralization [27,32]. However, other studies did not observe increased resistance of infant viruses to neutralization by maternal plasma [14,63,69,70]. Furthermore, no difference in sensitivity to autologous neutralization was observed between clade C viruses from postnatally-infected infant and viruses from their mothers [28].…”
Section: Discussionmentioning
confidence: 72%
“…In support of this hypothesis, previous studies reported that viruses transmitted during breastfeeding are usually resistant to maternal autologous neutralization [27,32]. However, other studies did not observe increased resistance of infant viruses to neutralization by maternal plasma [14,63,69,70]. Furthermore, no difference in sensitivity to autologous neutralization was observed between clade C viruses from postnatally-infected infant and viruses from their mothers [28].…”
Section: Discussionmentioning
confidence: 72%
“…Although the FcRn receptor binds monomeric IgG more avidly than aggregated or immunocomplexed IgG the mechanism may provide a route whereby HIV-1/anti-HIV-1 IgG complexes can be transferred to the fetus [35]. Total IgG binding to gp160, gp120 glycoproteins and/or peptides derived from V3 or gp41 was measured in TM and NTM individuals with better binding found in the TM, which may be in line with heightened enhancement to transcytosis of HIV-1 via HIV/IgG complexes [12],[36][38]. In addition, it has been demonstrated in studies utilizing a trophoblast monolayer model mimicking the barrier between the placenta and fetal blood that the fusion of HIV-1 infected PBMCs, monocytes and macrophages at the apical side of the monolayer can be followed by HIV-1 transcytosis to the lateral side [35], [39].…”
Section: Introductionmentioning
confidence: 74%
“…Reports on human mother child pairs have shown better neutralization by NTM than by TM suggesting a protective role by Abs [24], [25]. Others report better neutralization by TM or find no differences between TM and NTM [12], [14], [18], [24], [26][29]. Neutralization resistance in children against mother’s plasma or serum has been reported suggesting transmission of neutralization escape mutants, but, in contrast, sensitivity for neutralization by plasma of the mother has also been found [18], [24], [26], [27], [30], [31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Animal studies have demonstrated that neutralizing antibodies elicited by a simian immunodeficiency virus (SIV) vaccine can at least slow disease progression (56), while direct administration of antibodies matched to the chal-lenge virus can block transmission (16,44). Studies of natural MCTC have yielded conflicting results (2,3,7,20,26,31,32,48), although possibly for identifiable reasons. The breadth of the neutralizing antibody response may depend on the subtype of HIV-1 being studied (5,10), and neutralizing antibody levels may be associated with the timing of transmission (3).…”
Section: Subtype C Human Immunodeficiency Virus Type 1 (Hiv-1c) Contimentioning
confidence: 99%